Improving Teacher Performance by Strengthening Personality, Organizational Culture, and Achievement Motivation - Zamroni, Zamroni; Hardhienata, Soewarto; Sunaryo, Widodo; Zainal Arifin, M.; Abidin, Zenal (Opción, 2019)
Teacher performance is an important element related to the achievement of educational goals. If the teacher’s performance is high then learning goes well and students get maximum learning. Preliminary observations made at state high schools in Muaro Jambi District indicate that teacher performance is still not as expected. Therefore the teacher’s performance is interesting to study. This study aims to find ways to improve teacher performance by examining the strength of personality, organizational culture and achievement motiva- tion with teacher performance. The method in this study is a correlational statistical method for analyzing the relationship between variables and the SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) method for analyzing indicators in order to de- termine the recommendations of research results. The study population of all Civil Servants (PNS) teachers in state high schools in Muaro Jambi Regency, Jambi Province, consisted of 13 schools with a total of 333 PNS teachers with a sample of 182 teachers taken by proportional random sampling. The results of this study concluded that there is a positive relationship between personality and teacher performance with a correlation coeffi- cient of 0.611, thus the higher the personality is predicted the higher the teacher’s performance. There is a relationship between organizational cul- ture and teacher performance by 0.616. There is a positive relationship be- tween achievement motivation and teacher performance by 0.441. There is a relationship between personality and organizational culture together of 0.637. There is a positive relationship between personality and achieve- ment motivation together with teacher performance of 0.627. There is a positive relationship between organizational culture and achievement motivation together with teacher performance of 0.624. There is a positive relationship between personality, organizational culture and achievement motivation together with teacher performance of 0.643. This indicates that teacher performance can be improved through strengthening person- ality, organizational culture and achievement motivation.